IN-SITU THERMAL DESORPTION PILOT STUDY TO TREAT CHLORINATED COMPOUNDS FROM A FORMER CHEMICAL MANUFACTURING FACILITY: THE USE OF PILOT STUDY DATA TO OPTIMIZE FULL SCALE DESIGN - GERARDO KESSEL, LOWELL; GECKELER, GRANT; HAEMERS, JAN; CARPENTER, CAVIS (Águas Subterrâneas, 2013)
Thermal Conduction Heating (TCH), Steam Enhanced Extraction and Electrical Resistance Heating form the most common In Situ Thermal Remediation (ISTR) techniques. Such ISTR techniques have been successfully demonstrated at >100 sites to worldwide, and have proven especially effective for addressing source zones with high concentrations of chlorinated and organic chemicals. Many of these projects are in urban environs, where rapid and certain redevelopment is desired without excavation. In Winter of 2012, TPS TECH completed a pilot-scale application of In-Situ Thermal Desorption (ISTD) – a combination of TCH and vacuum – to treat of chlorinated volatile organic compounds (chlorobenzenes) in low to moderate permeability clays A small group of 14 thermal wells heated the 120 m3, 5 m deep target treatment zone, to an average temperature of 200°C in 30 days. Despite the low permeability of the treated volume, soil vapour extraction exaggerated by steam stripping was the dominant removal mechanism of the chlorinated compounds. Superheated temperatures above the boiling point of water resulted in additional mass being recovered as the vapour pressure of the chlorinated compounds continued to increase with temperature, resulting in a >98% reduction in chlorinated VOCs. Based on the successful pilot study results, the full scale treatment of chlorinated compounds is currently being constructed onsite to treat 2,100 cubic meters of source zone soils via ISTD.